Forest damage in the eyes of scientists - Jägerborg, Maria (2022)
Forest damage is a complex concept. Damaging agents appear naturally in ecological systems, but forest management also impacts their quantities. Damage can also be viewed from its interactions with a social system, where it appears and is understood. How we pre-empt forest damage is crucial, since it predefines the extent to which forests can contribute to the fulfilment of humans’ contradictory needs. Forest researchers in different scientific fields face the complexity of forest damage in their work, they are thus both impacted and impacting how the concept is understood and represented. This project explores the conceptualization of ‘forest damage’ in scientific practice by exploring the frames of damage problems. The analytical framework of the study combines the concepts of frames, narratives and discourses to guide versatile qualitative exploration of forest damage as perceived by forest scientists. The ‘frames’ of informants’ perceptions of damage are linked to wider environmental discourses, finally producing a chronological narrative. The study builds on qualitative interviews with 12 researchers from Swedish universities representing three scientific fields, namely silviculture, ecology and damage agent specialists. The analyses of interview data were supported by literature studies. The results show that, in a ‘mainstream’ interpretation, forest damage has been a traditional silvicultural concept defined by a utilitarian perspective on forests. The increasing societal recognition of diverse forest functions contributes to the expansion of the concept from a pure production-focus to an incorporation of damage caused to ecosystem services and biodiversity. Frame analysis revealed three perspectives in damage management labelled silviculture-, industryand system perspective. The framing of damage problems by ‘calculated-risk taking’ i.e. willingness to accept ‘reasonable’ and cost-efficient risk of damage, is found to constitute the ideological core for how damage is approached in Swedish forestry. This framing impacts the interest in damage research and the conditions for finding research solutions to damage problems. The ‘calculated risktaking’ frame mainly captures the interests of industrial owners rather than of small non-industrial private forest owners. Environmental concerns also impact priorities in damage management and they require pollution-free management solutions. ‘Ecological modernization’ and ‘neo-liberalism’ are underlying discourses found to be structuring the industry perspective. During the last five decades the traditional silvicultural perspective has been challenged first by the industry perspective and recently by the system perspective. Most researchers in this study ask for a more holistic and adaptive perspective of forest damage. They suggest to spread risks through diversifying the management. Results of this project can be used to improve dialogue about priorities in damage research and management.